Planning for the Effects of Sea Level Rise in Western Australia - Robb, Ashley John (Curtin University, 2019)
This research examines the potential role of urban planning in helping communities adapt to sea level rise induced hazards such as inundation, storm erosion and shoreline recession, in Western Australia’s urban areas. Applying a qualitative mixed-methods approach, the research finds that modifications to the state coastal planning framework, including associated legislation and existing funding programs, will be needed to enable public authorities to adequately plan and manage for these hazards as sea level rise accelerates.